Peningkatan Daya Saing Toko Bangunan Sumber Rejeki Kabupaten Blitar Melalui Strategi Pemasaran Berbasis Analisis SWOT - Nabilatul Badi’ati; Zulistiani Zulistiani (Universitas Nusantara PGRI Kediri, 2023)
Sumber Rejeki Building Store is a trading company engaged in retail by selling various kinds of building materials such as cement, paint, nails, iron and so on. The purpose of this study was to analyze the internal and external environment of the Sumber Rejeki building store and to find out the marketing strategy that should be implemented in order to increase competitiveness. This study uses a type of qualitative research with SWOT analysis techniques. Collecting data in this study using observation techniques, interviews, and documentation. The results of the study show that in the SWOT diagram the Sumber Rejeki building store is in quadrant I, which means that this company has the strength to take of existing opportunities, so the marketing strategy that should be used to increase competitiveness is the SO (Strengths-Opportunities) strategy by carrying out several strategies such as maintaining and improving product quality and good service to consumers, building a special place for building design consulting services, offering discounts or gifts with a certain purchase amount especially to customers who have frequently shopped at the store, and updating the latest products so that they continue to grow and dominate market share.